EVALUASI KEBIJAKAN DI BADAN PERENCANAAN PEMBANGUNAN PENELITIAN DAN PENGEMBANGAN (BAPPELITBANG) KOTA BANDUNG : (Studi: Perda Nomor 18 Tahun 2011 tentang RTRW Kota Bandung tahun 2011-2031) - Mariane, Ine; Prasasti, Ajeng Setia (Prodi Administrasi Publik FISIP UNPAS, 2023)
The issuance of Regional Regulation No. 18 of 2011 concerning the Spatial Planning of the City of Bandung in 2011-2031, became a direction for the Bandung city government in carrying out spatial planning for the city of Bandung which is growing rapidly so that it has an impact on the emergence of various city problems that require solutions. BAPPELITBANG Bandung city as a regional apparatus is tasked with facilitating the development of infrastructure and regional areas which includes the planning, implementation and evaluation process of implementation. The purpose of this study was to determine the process of systematic evaluation of policies at BAPPELITBANG Bandung (study: Perda No.18 of 2011 concerning the RTRW of Bandung City in 2011-2031). The research method uses qualitative research with a case study approach. Data collection techniques in the form of observation, interviews, and documentation. The results of the study show that the implementation of this regional regulation is quite good, it can be seen from good planning and has been implemented, but there are also plans that have been implemented but still cannot solve the problems that exist in the city of Bandung, especially in infrastructure development and regional development so that revisions must be made in the city of Bandung. this regulation.